Staged IVC venous sampling for ACTH in a Von-Hippel-Lindau syndrome (VHL) patient with Cushing's syndrome, pancreatic neuroendocrine tumor and renal cell carcinoma - Haydar Ali Tajuddin, Amalina; Kamaruddin, Nor Azmi; Sukor, Norlela; Mustafa, Norlaila; Abdul Wahab, Norasyikin (2018)
Introduction Outlining the source of ACTH in a VHL patient with Cushing's syndrome can be quite challenging as the origin of the hormone could either come from the pancreatic neuroendocrine tumor (NET) or the renal cell carcinoma (RCC). Case description A 31-year-old lady with type 2 diabetes, who was in her second trimester of third pregnancy, experienced rapid weight gain and accelerated hypertension. She had florid features of Cushing’s syndrome with a family history of VHL. Initial laboratory results revealed potassium of 2.5 mmol/L, bicarbonate 30 mmol/L and morning cortisol of 2823 nmol/L. Her serial 24-hour urine cortisol ranged from 1122-14710 nmol/L together with elevated ACTH level (18.8 pg/ml) and serum Chromogranin A (530.2 ng/mL). Repeated urine cathecolamines were otherwise normal. She had caesarean section at 28 weeks gestation due to placental insufficiency. Post-delivery hypercortisol state was controlled by oral Ketoconazole 400mg TDS and oral Metyrapone 250mg TDS. MRI Pituitary did not show any discernible pituitary lesion. CT abdomen revealed complete replacement of the pancreas by mixed solid and cystic lesions measuring 2.5 to 4.0cm. There was also solid mass seen in the midpole of right kidney measuring 3.7 x 2.5 x 4.0 cm. A super selective sampling of the IVC for ACTH together with bilateral inferior petrosal sinus sampling was performed to delineate the source of ACTH. ACTH level arising from the hepatic vein that was corresponding to the pancreatic drainage was higher than the rest. Total pancreatectomy and right nephrectomy were done. The histopathological examination revealed mixed-serous pancreatic NET with RCC. Glucocorticoid replacement and Creon were commenced after surgery. Conclusion In a VHL patient with Cushing's syndrome and the presence of both pancreatic NET and RCC, a selective venous sampling of IVC is an important work up to delineate the source of ACTH.